OOPS, Turning MIT Opencourseware into Chinese: An analysis of a community of practice of global translators - Mimi Miyoung Lee (Athabasca University Press, 2007)
An all-volunteer organization called the Opensource Opencourseware Prototype System (OOPS), headquartered in Taiwan, was initially designed to translate open source materials from MIT OpenCourseWare (OCW) site into Chinese. Given the recent plethora of open educational resources (OER), such as the OCW, the growing use of such resources by the world community, and the emergence of online global education communities to localize resources such as the OOPS, a key goal of this research was to understand how the OOPS members negotiate meanings and form a collective identity in this cross-continent online community. To help with our explorations and analyses within the OOPS translation community, several core principles from Etienne Wenger’s concept of Communities of Practice (COP) guided our analyses, including mutual engagement, joint enterprise, shared repertoire, reification, and overall identity of the community. In this paper, we detail how each of these key components was uniquely manifested within the OOPS. Three issues appeared central to the emergence, success, and challenges of the community such as OOPS: 1) strong, stable, and fairly democratic leadership; 2) participation incentives; and 3) online storytelling or opportunities to share one’s translation successes, struggles, and advice within an asynchronous discussion forum. While an extremely high level of enthusiasm among the OOPS members underpinned the success of the OOPS, discussion continues on issues related to quality control, purpose and scope, and forms of legitimate participation. This study, therefore, provides an initial window into the emergence and functioning of an online global education COP in the OER movement. Future research directions related to online global educational communities are discussed.